2014
DOI: 10.18052/www.scipress.com/ilns.17.194
|View full text |Cite
|
Sign up to set email alerts
|

Increased Production of Carrageenase by <i>Pseudomonas aeruginosa</i> ZSL-2 Using Taguchi Experimental Design

Abstract: The culture conditions for the production of carrageenase were optimized using one-factor-at-atime method combined with orthogonal array design. With the one-factor-at-a-time method revealed optimal conditions for carrageenase production were 24 h of fermentation period, 28 °C incubation temperature at pH 8.0 with NaNO 3 as nitrogen source and carrageenan as carbon source in MMS media. Further optimization of carrgeenase production by using orthogonal experimental design L 9 (3 4 ) with four factors, temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…In L 9 orthogonal array method only 9 experiments were performed whereas, if factorial experimental design International Letters of Natural Sciences Vol. 17(Planket Burner design and central composite design) was used, at least 81 experiments in triplicate would be necessary to achieve the same results. Very few reports have described the optimization of agarase production using one factor at time method [10,12,14] reported optimisation of agarase production by statistical strategy using combination of Planket Burner design and central composite design (CCD).…”
Section: Experimental Results Of L 9 (3 4 ) Orthogonal Matrix Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In L 9 orthogonal array method only 9 experiments were performed whereas, if factorial experimental design International Letters of Natural Sciences Vol. 17(Planket Burner design and central composite design) was used, at least 81 experiments in triplicate would be necessary to achieve the same results. Very few reports have described the optimization of agarase production using one factor at time method [10,12,14] reported optimisation of agarase production by statistical strategy using combination of Planket Burner design and central composite design (CCD).…”
Section: Experimental Results Of L 9 (3 4 ) Orthogonal Matrix Methodsmentioning
confidence: 99%
“…This strain was routinely maintained and stored at 4 °C on MMS-agar slants in the laboratory. Seed culture was prepared from 24h grown culture on MMS liquid broth at 180 rpm and 37 °C as reported earlier [17].…”
Section: Microorganismmentioning
confidence: 99%
“…In this regard, studies on important carrageenan degraders reported in the recent years are listed in Table 2. Among bacteria, degradation is mostly confined to Gram negative, mainly various Pseudoalteromonas, Cellulophaga, Pseudomonas, Cytophaga, Tamlana, Vibrio, Catenovulum, Microbulbifer, Zobellia, Alteromonas (Shangyong et al 2013; Yao et al 2013; Ziayoddin et al 2014; Mou et al 2004; Feixue et al 2010; Li et al 2015; Hatada et al 2011; Liu et al 2013; Michel et al 2001b; Zhu and Ning 2016). However, some Gram positive bacteria like Bacillus sp.…”
Section: Sources Of Carrageenasesmentioning
confidence: 99%
“…QY3Iota-carrageenan/25 °C/150 rpm/20 h/pH 7.050>80 %/50 °C/pH 7.0/60 min7.0>70 %/pH 5.0–10.6/720 min/4 °C48.3 kDaMa et al (2013)11 Cytophaga lk-C783ZM g having carrageenan/25 °C/150 rpm/72 h25 °C50 %/50 °C/pH 7.0/10 min7.6NR n 100 kDaSarwar et al (1983a, b, 1987)12 Cytophaga MCA-2ZM g having carrageenan/32 °C/150 rpm/36 h/pH 7.5280 %/55 °C/30 min7.232 %/pH 10.83/24 h30 kDaMou et al (2004)13Dsij strainZM g /22 °C/250 rpm/24–40 h40100 %/30 °C/pH 7.2/120 min7.2100 %/7.0/60 min/40 °C40 kDaPotin et al (1991)14Marine bacteriaCarrageenan/20 °C–25 °C/100 rpm/72–96 h40NR n 7.5NR n NR n Yaphe and Baxter (1955)15 Pseudoalteromonas sp. QY203Kappa-carrageenan/25 °C/150 rpm/48 h4570 %/35 °C/pH 7.2/48 h7.2>70 %/6.5–9.0/6 h/4 °C34Shangyong et al (2013)16 Pseudomonas aeruginosa ZSL-2Kappa-carrageenan + MMSM h /37 °C/180 rpm/24 h28NR n 8.0NR n NR n Ziayoddin et al (2014)17 Pseudoalteromonas strain CL19Kappa-carrageenan/20 °C/72 h…”
Section: Sources Of Carrageenasesmentioning
confidence: 99%
See 1 more Smart Citation